Investigation of the effect of nanofluids on heat transfer enhancement by using parallel and vertical springs in a plate heat exchanger - Peker, Gokce; Yildiz, Cengiz; Cakmak, Gulsah; Yildiz, Ahmet (Springer, 2023)
iota This research presents an experimental study on the thermal performances of a counterflow plate heat exchanger using Al2O3/water and CuO/water nanofluids at different weight ratios. Springs were placed vertical and parallel to the plate to create turbulence in the flow. Al2O3/water and CuO/water nanofluids were produced using the two-step method with three nanoparticle weight fractions (0.1%, 0.5% and 1%). Within the ranges studied, the Al2O3-water nanofluid provides maximum improvement in heat transfer coefficient of about 76.1% in the parallel spring plate heat exchanger compared to the base fluid. For the same mass ratio and spring arrangement, this increase rate is 69.9% in the CuO-water nanofluid. The highest performance factor was determined when Al2O3-water nanofluid was used in the spring arrangement, whose springs were placed parallel to the channel at a flow rate of 5.5 lt/min, and this value was found to be 1.51.
Keywords: Pressure-Drop; Performance